Determinant factors of competitiveness for the positioning of the artisanal sector - Sifuentes, Lucia Guadalupe Panta; Troncoso, Alberto Samuel Monzon; Apaza-Panca, Cynthia Milagros; Rosa, Patricia Elena Ramos La; Cadillo, Ana Juliani Rodriguez (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this research was to understand the competitiveness factors that determine the positioning of the artisanal sector in a Peruvian city. The methodology used in the study followed a quantitative and explanatory approach, based on the analysis of relationships between variables through Structural Equation Modeling (SEM) to analyze the relationship between latent and observable variables. The population consisted of 82 artisans from the Lima Region of Peru, who were administered a 15-item Likert-scale instrument. The study determined that business competitiveness is related to the positioning of the artisanal sector in the Lima Region (β=0.761), confirming that greater business competitiveness leads to better market positioning. In this context, customer negotiation (β=0.024), the presence of substitute products (β=0.375), the emergence of new competitors (β=0.329), and the presence of current competitors (β=0.281) are significant determining factors that suggest the success of the artisanal sector. On the other hand, the explained variance (R²) for business competitiveness is 0.602, which means that 60.2% of its variability is determined by the variables in the model. Competitive positioning, for its part, has an R² of 0.578, indicating that 57.8% of its variability depends on business competitiveness, thus reinforcing their close relationship. This implies that the growth of the sector does not depend solely on creative talent or tradition, but on a business vision that allows anticipating market dynamics and differentiating itself in a constantly evolving competitive environment. Likewise, the sector must guarantee competitive prices for raw materials and strengthen the global handicraft value chain.